Nutcracker syndrome – patophysiology, diagnosis and treatment options: a literature review - Roś, Bartosz; Siekaniec, Katarzyna; Kuchenbeker, Natalia; Dojs, Adriana; Mierzwińska-Mucha, Julia; Jakubowicz, Magdalena (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Nutcracker syndrome (NCS) is a rare disorder resulting from renal venous hypertension as a consequence of external compression on the left renal vein (LRV). Because of its non-specific symptoms, it still presents as a diagnostic and therapeutic challenge. In the current literature there is no consensus on clear diagnostic and therapeutic pathway. We conducted a review of the literature to gather and systematize knowledge about this disease in order to describe its etiology, diagnostics and treatment options. A brief description of the state of knowledge: NCS is a disorder that should be considered in the differential diagnosis of abdominal conditions causing left flank pain, hematuria and proteinuria. Nowadays, the most common first-line diagnostic technique is Doppler ultrasound examination but in most cases it must be confirmed by computed tomography, magnetic renonanse imaging or invasive venography. In some patients suffering from NCS, withdrawal of symptoms can be achieved by conservative treatment but sometimes it is insufficient. The most frequent surgical treatment method for this syndrome is LRV transposition, sometimes combined with great saphenous vein auto-graft. Other invasive techniques include left gonadal vein transposition, kidney autograft, nephrectomy or endovascular treatment. Summary: Although NCS has been known for a long time, widely accepted diagnostic and treatment criteria are yet to be developed. Physicians can use several treatment options but the choice often depends on individual clinical presentation and preference. Many issues, for example role of aspirin or renal autotransplantation, still require extensive research.